THE ONLINE SENSORIAL EVALUATION OF FOOD - Triatma, Bambang (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2017)
One of the subjects in the vocational education is the analysis of the food quality by sensorial evaluation. The sensorial evaluation of food is usually done by humans in a laboratory where used "panelists came to food" approach. This approach is very bound by the schedules, seized the place and disrupt the daily schedule of panelists as students. When there is no match meeting, free time varies between the panelists and researchers, it needs the reverse approach where "food came to panelist". On this new approach, panelists tasted the food in other place then send the data online from each place. An online framework is required to implement this approach, which facilitates the sensorial serving panelist pour their sensorial response into keyboard beats and data will be directly delivered to researcher computer. Practitioners utilize collaborative space from provider https://bambangtriatma.wikispaces.comandhttps://kwiksurveys.comto perform the evaluation of the food as part of the courses the analysis of the food quality. One of the stages in the evaluation of food is researching the reliability of prospective panelists in judging the food. There are many aspects of the food sensorial characteristic: taste, flavor, texture and color, but color is the most already digitally judged than the other aspects. Therefore, at the beginning, the color aspect was first choosed by this system. Sensitivity of the prospective panelists against color examined their ability to identify the color of adjacent characters, then asked to decide whether the pair of different color or not. This approach is easy to doby computer screen thanks to the existence of a system of colors digitally mapping. Data is forwarded via the internet network with specific applications. This system makes it easy for researchers in the future to recruit prospective panelists as well asdoing the actual sensorial testing.